Family embeddedness and entrepreneurship experience: a study of Indian migrant women entrepreneurs in Australia. Issue 9 (19th October 2016) - Azmat, Fara; Fujimoto, Yuka
Abstract: India has emerged as a major source of migrants for developed countries including Australia; yet, there is a dearth of research on Indian migrant entrepreneurs, particularly women. Using qualitative methods of enquiry, we explore the perceptions of Indian migrant women entrepreneurs (MWEs) and their partners in Melbourne, Australia, about their entrepreneurship experiences from a family embeddedness perspective. More specifically, we explore how family embeddedness of Indian MWEs is influenced by certain factors which in turn influence their entrepreneurship experience. Our findings suggest that entrepreneurship among Indian MWEs is a complex phenomenon influenced by their being an Indian, a woman and a new Australian, all of which interact and influence their family dynamics and entrepreneurial experience. Our findings shed light on the duality of Indian culture which exerts both an enabling and a constraining influence on the family dynamics of MWEs, the constraining role of gender and the positive impact of their integration into the host country's sociocultural context which all influence their family embeddedness and entrepreneurship. Contributing to the discussion on 'ethnic' and 'women entrepreneurship' from a family embeddedness perspective, we offer policy implications for facilitating entrepreneurship in the growing but under-researched cohort of Indian MWEs.